Consent to Organ Donation: A Review. (March 2013) - Siminoff, Laura A.; Agyemang, Amma A.; Traino, Heather M.
Successful transplant medicine hinges on consent to deceased organ donation. Yet rates of consent remain suboptimal. To increase the availability of transplantable organs, several policy strategies along with a rich body of evidence aimed at identifying best practices for obtaining consent have accumulated. This review describes past and current policies and practices, presents evidence illustrating the impact of these policies and practices on consent, and summarizes future directions and recommendations for the field. Key findings include evidence that although past policies such as required request have been unsuccessful, the recent policy, first-person authorization, shows promise. Additionally, practices such as decoupling and detailed discussions of brain death are unwarranted. On the other hand, the Organ Donation Breakthrough Collaboration was successful. We also underscore the impact of alternative procedures such as donation after cardiac death. Last, effective communication that is delivered by trained, caring requesters at the appropriate time, in a supportive environment, and allows sufficient time for families to make an informed decision, optimizes the request process. Organ procurement organizations' adoption of such request practices, implementation of evidence-based policies regarding donation after cardiac death, and further investigations of the medical basis for dual brain death examinations are recommended.